The Relationship Between Energy and Protein Intake with The Nutritional Status of Children Aged 7-18 Years at Griya Sahabat Yatim Dhuafa in Gedangan Sidoarjo - Erika Deanita Ramadhani; inne soesanti; nur hatijah; Nurul Hindaryani (Politeknik Kesehatan Kemenkes Surabaya, 2024)
At the age of 7-18 years, consumption of carbohydrates as a source of energy and consumption of protein sources greatly affects their nutritional status. There are several foster children at GSY Dhuafa who are facing nutritional problems due to insufficient nutrition from food that is rich in energy and protein content. This study aims to determine whether there is a relationship between energy and protein intake with the nutritional status of foster children At GSY Dhuafa in 2023. Using a cross-sectional research method with a sample of 35 children using a total sampling technique. Data analysis in this study used univariate and bivariate analysis with the Chi-square test. From the research that has been done, the results show that there is a strong relationship between the adequacy of energy and protein nutrition and nutritional status (p=0.000), while protein intake has results (p=0.354), which means that there is no relationship between protein and nutritional status. There is a relationship between energy intake and nutritional status and there is no relationship between protein intake and the nutritional status of the respondents. It is expected to pay more attention to intake to meet nutritional needs in order to achieve good nutritional status.